INSTAGRAM AS A BALINESE CULTURAL CONSERVATION SOLUTION FOR MILLENNIALS - Hanindharputri, Made Arini; Putra, I Komang Angga Maha (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Visual communication design is medium for delivering the information needed by the society. In the present era, moreover with the existence of global disruption, information with visual communication is no longer done by offline, but already through digital media, such as social media. With the number of users dominated by millennials, social media such as Instagram become an effective communication media as visual marketing in promoting or campaigning a product. Social media content which is user-generated content presents various types of information that is interesting to millennials.  Starting from content related to hobbies, entertainment, to culture and tradition. In Bali, much social media account on Instagram contain culture and traditions to invite the younger generation to be more literate in all cultural products and activities. Information presented visually provides engagements such as the high number of views, likes, and comments. This can be caused by the concise of information, easy communication but still has an educational side. The positive impact that was finally felt by the millennials was the information relating to Balinese Culture was presented in real-time that make them easier to understand the cultural heritage that published through Instagram. So indirectly, the account becomes a cultural conservation agent enjoyed by the millennial generation to maintain the existence of the Balinese culture.